2017
DOI: 10.1111/bor.12225
|View full text |Cite
|
Sign up to set email alerts
|

Species identification and decay assessment of Late Pleistocene fragmentary vertebrate remains from Pin Hole Cave (Creswell Crags, UK) using collagen fingerprinting

Abstract: Ancient bone remains are widely utilized when investigating vertebrate biodiversity of past animal populations but are often so highly fragmented that the majority of specimens cannot be identified to any meaningful taxonomic level. Recently, high‐throughput methods for objective species identification using collagen peptide mass fingerprinting have been created to overcome this with the added indication that they could also offer a means of relative ageing through decay measurement. Here we explore both speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 48 publications
2
61
1
Order By: Relevance
“…Collagen fingerprinting has emerged as an important technique for archaeologists and Quaternary scientists, and this molecular tool is particularly useful for zooarchaeological identifications. Although several recent studies have demonstrated the value of this technique, many of these focus on terrestrial (Buckley et al 2016(Buckley et al , 2017 or marine mammals (Buckley et al 2014;Evans et al 2016;Hufthammer et al 2018), with comparatively limited attention, albeit growing, to fishes (Richter et al 2011;Harvey et al 2018). Our study is the first to use collagen fingerprinting for species identification of billfish, and points to the potential value of these data for helping understand prehistoric fisher encounter rates with various species and, if combined with archaeological evidence, ritual, and cultural variables.…”
Section: Resultsmentioning
confidence: 85%
“…Collagen fingerprinting has emerged as an important technique for archaeologists and Quaternary scientists, and this molecular tool is particularly useful for zooarchaeological identifications. Although several recent studies have demonstrated the value of this technique, many of these focus on terrestrial (Buckley et al 2016(Buckley et al , 2017 or marine mammals (Buckley et al 2014;Evans et al 2016;Hufthammer et al 2018), with comparatively limited attention, albeit growing, to fishes (Richter et al 2011;Harvey et al 2018). Our study is the first to use collagen fingerprinting for species identification of billfish, and points to the potential value of these data for helping understand prehistoric fisher encounter rates with various species and, if combined with archaeological evidence, ritual, and cultural variables.…”
Section: Resultsmentioning
confidence: 85%
“…We used matrixassisted laser desorption/ionization mass spectrometry to determine the relative mass-to-charge (m/z) values of the tryptic digest peptides in each bone sample. By comparing these values with a library of known fauna, we identified bones to genus or species in some instance (27)(28)(29)(30)(31). We screened a total of 383 unidentified bone samples from Vindija Cave (levels G1, G3, and stratigraphic unit G1-G3).…”
Section: Methodsmentioning
confidence: 99%
“…While such degradation complicates the analysis of collagen, it also enables one to study the myriad changes that an archaeological protein sample undergoes and potentially relate them the age and/or preservation of the sample under consideration (Buckley et al . ). Two of the most common structural changes observed in archaeological proteins include racemization and deamidation, the latter of which can be observed in a ZooMS fingerprint.…”
Section: Introductionmentioning
confidence: 97%
“…, 204) and is effectively used to identify outliers among a particular bone deposit (Buckley et al . ).…”
Section: Introductionmentioning
confidence: 97%